Literacy development in Malaysian schools with reference to creative writing throgh the method of action research. - Syed Ahmad, Syed Idrus (1996)
Most of the teaching objectives in Malaysian· schools are centred on preparing students to face their respective examinations when the time comes. Teachers are in jubilant mood if students show remarkable achievement in these examinations.